Comment on "Differential Effects of MitoVitE, α-Tocopherol and Trolox on Oxidative Stress, Mitochondrial Function and Inflammatory Signalling Pathways in Endothelial Cells Cultured under Conditions Mimicking Sepsis. Antioxidants 2020, 9(3), 195" - Karl J. Hegarty; Frances L. Byrne (MDPI AG, 2020)
Minter, B [...]